PENGARUH INFLASI, SERTIFIKAT BANK INDONESIA SYARIAH (SBIS), DAN KURS TERHADAP DANA PIHAK KETIGA (DPK) PERBANKAN SYARIAH DI INDONESIA - Kristina, Ika; Esya, Lavlimatria (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of inflation, SBIS, and exchange rate variables on funds in Islamic banking in Indonesia for the 2014-2019 period. The research method used is the quantitative method of multiple linear regression (OLS), by first doing the classical assumption test. The data used is time series, data from 2014-2019 sourced from the official website of Bank Indonesia and the Financial Services Authority. The data used are monthly data for 5 years with a total of 288 observations. The results showed that the OLS model passed the classical assumption test. The partial test of the independent variable inflation has a negative and significant effect, SBIS and the exchange rate have a positive and significant effect on TPF. For the simultaneous test results indicated by adjusted R-square 86.6%, which means that as many as 86.6% of the independent variables affect the dependent variable of TPF, and are significant, while the other 13.4% are explained by other variables not included in the research model.